جیلانی بانو کے ناولوں میں تانیثیت: FEMININE CONSCIOUSNESS IN JILANI BANO'S NOVELS (Al-Aasar, 2025)
This article is an Urdu fiction writer who has made the domestic and social life of Jilani Bano women and their problems in all herliterary works. The time when she started her literary life was the last period of the rise of the Progressive movement. Hyderabad Deccan (India) was going through a period of political chaos and emergency. The feudal environment and society were ending. In her novels Aiwan-e-Ghazal (1976) and Barish-e-Sang(1985), she has made the subject of women's helplessness, psychological problems and exploitation in the decadent feudal society. Where women are considered speechless and second-class creatures. Her freedom is taken away by imposing unnecessary restrictions. They are considered as a mere means of sexual indulgence. In the feudal system, such words are used for men and women which prove that men are superior and women are inferior. In the light of the ideas expressed the novels Aiwan-e- Ghazal an